'We don't know what tomorrow will bring': Parents' experiences of caring for a child with an undiagnosed genetic condition. (22nd March 2021) - Aldiss, Susie; Gibson, Faith; Geoghegan, Sophie; Jewitt, Anna; Elliott, Tara Kerr; Williams, Anna; Wray, Jo; Oulton, Kate
Abstract: Background: Families and healthcare professionals caring for a sick or disabled child without a definitive diagnosis face unique challenges, particularly in relation to managing uncertainty, access to healthcare and coordination of care. There has been little research exploring the impact this has on families, their support needs or their experience of health services. Methods: This qualitative interview study included interviews with 14 mothers of children with undiagnosed genetic conditions. Transcripts were analysed using thematic analysis. Results: Four themes emerged, uncovering overlapping patterns in the data: (1) living with complexity amidst uncertainty—'We don't know what tomorrow will bring'; (2) parental role—'I do everything I can'; (3) parental role—'Not coping is not an option'; and (4) support needs—'There's lots of help that just isn't out there'. Conclusions: The results clearly demonstrate the stresses faced when caring for a child with an undiagnosed genetic condition. Some themes are shared with the experience of other families caring for children with complex needs. However, parents were doing all they could for their child in the context of a life of uncertainty, with the absence of a clear diagnosis clearly causing additional stress that impacted on the whole family. Impact on their emotional and physical well‐being was evident; they described times of feeling stressed, worried and anxious. They were confused due to being overloaded with information and frustrated by a lack of care coordination. Parents did not appear to prioritize their own well‐being and held back their emotions to protect themselves and others. As a result, they had many unmet needs, particularly relating to emotional support.